Disorganized behavior on Link's cube test is sensitive to right hemispheric frontal lobe damage in stroke patients - Kopp, Bruno; Rösser, Nina; Tabeling, Sandra; Stürenburg, Hans Jörg; De Haan, Bianca; Karnath, Hans-Otto; Wessel, Karl (Frontiers in Human Neuroscience, 2014)
One of Luria’s favorite neuropsychological tasks for challenging frontal lobe functions was Link’s cube test (LCT). The LCT is a cube construction task in which the subject must assemble twenty-seven small cubes into one large cube in such a manner that only the painted surfaces of the small cubes are visible. We computed two new LCT composite scores, the constructive plan composite score, reflecting the capability to envisage a cubical-shaped volume, and the behavioral (dis-) organization composite score, reflecting the goal-directedness of cube construction. Voxel-based lesion-behavior mapping (VLBM) was used to test the relationship between performance on the LCT and brain injury in a sample of stroke patients with right hemisphere damage (N = 32), concentrated in the frontal lobe. We observed a relationship between the measure of behavioral (dis-) organization on the LCT and right frontal lesions. Further work in a larger sample, including left frontal lobe damage and with more power to detect effects of right posterior brain injury, is necessary to determine whether this observation is specific for right frontal lesions.